Cordingley, A. & Frigau Manning, C. (Eds.). (2017). Collaborative translation: From the Renaissance to the digital age. London/New York: Bloomsbury Academic. 272pp. - Liang, Linxin; Xu, Mingwu (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Book review